Answer:
(1 - 4x)³
Step-by-step explanation:
The first 2 terms are a difference of cubes and factor in general as
a³ - b³ = (a - b)(a² + ab + b²), thus
1 - 64x³
= 1³ - (4x)³
= (1 - 4x)(1 + 4x + 16x²)
Thus
1 - 64x³ + 48x² - 12x ← factor out 12x from each of the 2 terms
= (1 - 4x)(1 + 4x + 16x²) + 12x(4x - 1) ← factor out - 1 from (4x - 1)
= (1 - 4x)(1 + 4x + 16x²) - 12x(1 - 4x) ← factor out (1 - 4x) from the terms
= (1 - 4x)(1 + 4x + 16x² - 12x)
= (1 - 4x)(1 - 8x + 16x²) ← perfect square
= (1 - 4x)(1 - 4x)²
= (1 - 4x)³ ← in factored form
Answer:
3.33 but he cant buy 3 and 1/3 of a bag of chips so 4
Step-by-step explanation:
So, to find the solution to this problem, we will we using pretty much the same method we used in your previous question. First, let's find the area of the rectangle. The area of a rectangle is length x width. The length in this problem is 16 and the width is 3, and after multiplying these together, we have found 48 in^2 to be the area of the square. Next, we can find the area of the trapezoid. The area of a trapezoid is ((a+b)/2)h where a is the first base, b is the second base, and h is the height. In this problem, a=16, b=5, and h=10. So, all we have to do is plug these values into the area formula. ((16+5)/2)10 = (21/2)10 = 105. So, the area of the trapezoid is 105 in^2. Now after adding the two areas together (48in^2 and 105in^2), we have found the solution to be 153in^2. I hope this helped! :)
Answer:
.shsnxbjsjJsjsiakzjxjisksjxjs
A is your answer
let me know if you have any questions